Comparison of investment-linked products in Singapore. - Chan, Peifang. (2008)
This project seeks to evaluate the comparability of Investment-Linked Products with the use of the Profit-Testing Model across insurance companies. The purpose is to examine the soundness of using the model for possible application from the policyholders’ perspective.